Strategi Penyiar Radio Sonora 102,6 Fm Palembang Dalam Menarik Minat Pendengar Dalam Program Acara Anda Meminta Kami Memutar (AMKM) - Muhammad Lindu; Sumaina Duku; Hartika Utami Fitri (CV. ITTC INDONESIA, 2023)
In the midst of the onslaught of the digital era, radio still exists today. The use of radio as a medium for conveying informations and as a place for preserving Indonesian cultures are decreasing due to the rapid development of technology and the swift currents of globalization. This is a challenge for radio broadcasters in determining the strategy used to maintain the existence of the radio. With the strategy of the announcer of Radio Sonora 102.6 FM Palembang in attracting listeners's interest in the You Ask We Play (AMKM) program, the researcher used qualitative methods through documentation, observation and interview approaches. From the results of the research that has been done, it can be concluded that the strategy used by the announcers of Radio Sonora 102.6 FM Palembang in attracting listeners's interest is to become a broadcaster who can use language that is easy to understand, polite, friendly, and most importantly make listeners as friends so that listeners feel comfortable and they can attract the interest of other listeners. In addition, the rapid development of technology has given rise to new, more sophisticated media, which became the main inhibiting factor in maintaining the existence of radio.